Working Hours for Women Labourers and the factors Afffecting: A Study on Rice Farming in Pondok Kubang District, Central Bengkulu Regency - Refita Rahmadini; M. Zulkarnain Yuliarso; Ketut Sukiyono (Demeter: Journal of Farming and Agriculture, 2025)
The involvement of women as rice farm labourers in Pondok Kubang District causes their working time to be divided into productive, domestic, social, and leisure activities, which are measured in hours per week. This study aims to analyse the working time of female rice farm labourers and the factors that influence it, including age, education, number of dependents, previous season's income, head of household income, and work experience of farm labourers. The study was conducted in December 2024 using a census technique on 102 respondents who worked on other people's rice fields. The analysis methods used include analysis of working time and multiple linear regression. The study's results showed that the average working time of female farm labourers in productive activities was 46.03 hours per week, for domestic activities 39.97 hours per week, for social activities 4.94 hours per week, and for leisure time 9.06 hours per week. Simultaneously, all independent variables have a significant effect. Partially, the variables of age, previous season's income, head of household income, and work experience have a significant effect, while education and number of dependents have no effect.